THE ADAPTIVE POTENTIAL OF TOMATO GENOTYPES TO LOW-TEMPERATURE STRESS BY TRAITS OF MALE GAMETOPHYTE - USM ADMIN (Studia Universitatis Moldaviae: Stiinte reale si ale naturii)
The paper presents the results of studying the effect of low temperature factor (+6°C) on the character of manifestation of male gametophyte traits under in vitro and in vivo conditions at different time exposures (from 1 to 60 days) of pollen storage of tomato genotypes. The dynamics of pollen quality changes and its fertilizing ability depending on storage time was shown. Tomato genotypes (L5, L7, Solaris, Nota), with high adaptive status of their pollen to the cold factor (+6°C), which after storage for 60 days retains the optimal percentage of viable pollen (8, 1%-12.4%), germinating equally well both on artificial nutrient medium and pistil stigmas, providing moderate fruit set (16.7-46.8%) and good seed formation (13-50.9%). This research approach can be effectively used to evaluate and identify genotypes with high adaptive potential for use as donors in breeding programs, as well as when multiple pollinations with pollen of genotypes with short flowering periods are required and especially in heterotic breeding for hybrid seed production. Keywords: Tomato, genotype, male gametophyte, low-temperature stress, shelf life, pollen viability, pollen tube length.